2013
DOI: 10.1021/ci400187y
|View full text |Cite
|
Sign up to set email alerts
|

Deep Architectures and Deep Learning in Chemoinformatics: The Prediction of Aqueous Solubility for Drug-Like Molecules

Abstract: Shallow machine learning methods have been applied to chemoinformatics problems with some success. As more data becomes available and more complex problems are tackled, deep machine learning methods may also become useful. Here we present a brief overview of deep learning methods and show in particular how recursive neural network approaches can be applied to the problem of predicting molecular properties. However molecules are typically described by undirected cyclic graphs, while recursive approaches typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
460
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(465 citation statements)
references
References 56 publications
(119 reference statements)
3
460
0
2
Order By: Relevance
“…It has been confirmed that deep-learning architectures have the power to handle big data with little manual intervention. 37,38 These practical and useful techniques also have been applied to chemoinformatics and bioinformatics [39][40][41][42][43][44][45][46][47][48][49] for dealing with different tasks, such as, aqueous solubility prediction, quantitative structure-activity relationship analysis, 48 and predicting the sequence specificities of DNA/RNA binding proteins. 50 Motivated by its great success in these fields mentioned above, we expect that DL is also practical and effective for DILI prediction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that deep-learning architectures have the power to handle big data with little manual intervention. 37,38 These practical and useful techniques also have been applied to chemoinformatics and bioinformatics [39][40][41][42][43][44][45][46][47][48][49] for dealing with different tasks, such as, aqueous solubility prediction, quantitative structure-activity relationship analysis, 48 and predicting the sequence specificities of DNA/RNA binding proteins. 50 Motivated by its great success in these fields mentioned above, we expect that DL is also practical and effective for DILI prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these solvation/hydration methodologies have been summarized in a recent review by Skyner et al 19 Commonly, QSPR methods are employed due to their speed, convenience and accuracy, when provided with a suitable training dataset. 10,[20][21][22]23 These methods represent the current state-of-the-art in practical solubility prediction. However, QSPR methods lack the theoretical basis of a fundamental physical theory, hence limiting their interpretability and the understanding that can be gained from their use.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many 'black box' solubility prediction models were reported in early years. Recently, Lusci et al (2013) reported an aqueous solubility prediction model based on undirected graph recursive neural networks (UG-RNNs) with deep architectures and deep learning. The main advantage of the UG-RNN approach is that it can automatically extract the internal representations from the molecular graphs, as suited for solubility prediction.…”
Section: Solubilitymentioning
confidence: 99%